2016
DOI: 10.1007/s40477-016-0207-4
|View full text |Cite
|
Sign up to set email alerts
|

Localized cervical pain: advantages and limits of ultrasound evaluation

Abstract: Ultrasound examination can be used as diagnostic tool in the evaluation of selected patients suffering from localized cervical pain, particularly in cases of pain due to traumatic injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Ultrasound is an excellent tool in "visualizing" and hence "avoiding" vascular injury especially during cervical spine procedures. 1 Studies on ultrasoundguided spine injection and CT scan confirmation of the needle tip showed feasibility and validity of ultrasound in spine injections. [2][3][4][5][6] Despite the introduction of newer and less consuming times methods 7 with the possibility of intravascular injection, there is still insufficient clinical evidence to prove the safety of the ultrasound as a sole image guide intervention, especially for transforaminal injection.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound is an excellent tool in "visualizing" and hence "avoiding" vascular injury especially during cervical spine procedures. 1 Studies on ultrasoundguided spine injection and CT scan confirmation of the needle tip showed feasibility and validity of ultrasound in spine injections. [2][3][4][5][6] Despite the introduction of newer and less consuming times methods 7 with the possibility of intravascular injection, there is still insufficient clinical evidence to prove the safety of the ultrasound as a sole image guide intervention, especially for transforaminal injection.…”
Section: Introductionmentioning
confidence: 99%